Characterization of Corosolic Acid as a KPC-2 Inhibitor That Increases the Susceptibility of KPC-2-Positive Bacteria to Carbapenems - Zhou, Yonglin; Lv, Xiaohong; Chen, Meishan; Guo, Yan; Ding, Rui; Liu, Bin; Deng, Xuming; Wang, Jianfeng (Frontiers in Pharmacology, 2020)
Abstract The emergence of KPC-producing Gram-negative bacteria in clinical practice highlights the need to search for novel antimicrobials and new anti-infection strategies. In this study, we constructed a laboratory KPC-2-positive strain, E. coli BL21(DE3) (pET28a-KPC-2) and identified the activity of KPC-2 in this strain. Using enzyme inhibition assays, checkerboard MIC assays, growth curves, time-killing assays and combined disk test, we found that the natural compound corosolic acid (CA) significantly inhibited the activity of the class A β-lactamase KPC-2, which is common among clinical isolates. CA treatment increased the antibacterial or bactericidal activity of imipenem and meropenem against E. coli BL21(DE3) (pET28a-KPC-2) in vitro (FIC index=0.17±0.03 for both carbapenems). In addition, the mouse intraperitoneal infection model confirmed that the combination therapy significantly reduced the bacterial load in the livers and spleens following subcutaneous administration. Our results showed that CA can be used to extend the life of carbapenems, providing a viable strategy for severe infections caused by KPC-2-positive bacteria.